[Pilgrim]age repositioned : reinvigorating technological, historical and natural significances in the museum-town of Pilgrim’s Rest - Barker, A.A.J. (Arthur Adrian Johnson) (University of Pretoria, 2023)
Mini Dissertation (MArch (Prof))--University of Pretoria, 2022.